Metallographic analysis of failure mechanisms during Nakajima tests for the evaluation of forming limits on a dual-phase steel - Affronti, Emanuela; Weidinger, Mario; Merklein, Marion (IOP Conference Series: Materials Science and Engineering, 2018)
The material characterization is the first step for an accurate numerical design of forming operations. Since its first definition in the 1960s, the forming limit curve (FLC), usually evaluated with Nakajima or Marciniak tests, is still one of the most used criteria in the industrial and scientific field for the determination of the forming limits under different stress conditions. Despite the several signs of progress in terms of measurement techniques, thanks to the introduction of optical measurement systems, the European standard method for the evaluation of the FLC remains the cross-section-method of 2008. This method is basically suitable for materials with a pronounced necking evolution. For materials with an abrupt localization, like modern high-strength materials, the standard evaluation shows weaknesses. Investigations in 2015 based on pattern recognition on Nakajima tests show that the pattern evolution of the strain distribution during the test can be used for the prediction of the material failure. However, a definition of the pattern development is needed. In order to investigate new possibilities for the determination of the FLC, the knowledge about the failure mechanisms during Nakajima tests for these materials has to be increased. The aim of the present work is an analysis of the changes on the surface and the microstructure during the Nakajima tests at different stress states and drawing depths. The correlation between material modifications and failure behavior is conducted on the dual-phase steel DP800. For the analysis of the surface and the thickness, the scanning electron microscope (SEM) is employed. Moreover, considerations about the forming mechanisms of the DP800 at different stress conditions are given and compared with the forming limit prediction of the FLC.
LFT Import::2019-07-29 (2326)